Pengaruh Debt to Equity Ratio dan Return On Equity Terhadap Nilai Perusahaan Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di BEI Periode 2015 – 2024 - Sahrial Aurelin Hakiki; Hidayat Asprilla Ikhsan (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the effect of Debt to Equity Ratio (DER) and Return on Equity (ROE) on Price Earning Ratio (PER) in mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2015–2024. The research method used is a descriptive quantitative approach with secondary data in the form of annual financial reports from five mining companies, namely PT Bukit Asam Tbk, PT Aneka Tambang Tbk, PT Alamtri Resources Indonesia Tbk, PT Indo Tambangraya Megah Tbk, and PT Vale Tbk. The results of the study indicate that there are significant variations in DER, ROE, and PER values ​​between companies. The classical assumption test proves that the regression model meets the validity criteria, such as normality, absence of multicollinearity, autocorrelation, or heteroscedasticity. These findings indicate that DER and ROE have a relevant influence on PER, so they can be used as important considerations by investors in assessing the value of a company.